2020
DOI: 10.1016/j.prp.2020.153228
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse alveolar damage and thrombotic microangiopathy are the main histopathological findings in lung tissue biopsy samples of COVID-19 patients

Abstract: Background Since the outbreak of the novel coronavirus disease-2019 (COVID-19) in December 2019, limited studies have investigated the histopathologic findings of patients infected with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Material and methods This study was conducted on 31 deceased patients who were hospitalized for COVID-19 in a tertiary hospital in Tehran, Iran. A total of 52 postmortem tissue biopsy samples were obtained from the lungs and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
2
26
0
1
Order By: Relevance
“…These findings included severe endothelial injury, widespread alveolar capillary fibrinous microthrombi (9-times more prevalent than in influenza-infected lungs) and marked features of (mainly intussusceptive) angiogenesis with formation of new vessels growing into the lumen of existing vessels [ 14 ]. Beigee et al described diffuse alveolar damage and thrombotic microangiopathies in lung biopsies of 31 patients who had died from COVID-19 [ 16 ]. Moreover, other autopsy studies confirmed extensive fibrinous microthrombi in the lungs [ 53 , 55 ] and also in some skin lesions [ 53 ], from patients succumbed to severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings included severe endothelial injury, widespread alveolar capillary fibrinous microthrombi (9-times more prevalent than in influenza-infected lungs) and marked features of (mainly intussusceptive) angiogenesis with formation of new vessels growing into the lumen of existing vessels [ 14 ]. Beigee et al described diffuse alveolar damage and thrombotic microangiopathies in lung biopsies of 31 patients who had died from COVID-19 [ 16 ]. Moreover, other autopsy studies confirmed extensive fibrinous microthrombi in the lungs [ 53 , 55 ] and also in some skin lesions [ 53 ], from patients succumbed to severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In line with laboratory surrogates of activated coagulation, COVID-19 is associated with increased rates of thromboembolic events in 15% up to 69% [ 9 , 10 , 11 , 12 , 13 ]. Autopsy studies have confirmed that large vessel thromboembolic events and microthrombosis contribute to structural lung damage and respiratory failure [ 14 , 15 , 16 ]. Disseminated intravascular coagulation (DIC), as identified by a diagnostic DIC score, was found in 15/21 (71.4%) patients with fatal outcome but only 1/162 (0.6%) survivors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…73,112,113 The notion of pulmonary circulation thrombosis induced by endothelial injury is supported by evidence that alveolar damage in COVID-19 is frequently accompanied by thrombotic microangiopathy (figures 1, 2). 114,115 COVID-19-associated endotheliopathy with diffuse microcirculatory injury in the lungs appears to be a central feature of the severe disease phenotype. We henceforth refer to this endotheliopathy-centred condition as endotheliitis, following the first use of this term by Varga and colleagues; 110 however, descriptions of the same or similar small-vessel COVID-19 pathology by the same authors and other investigators have included the terms angio centric lymphocytic inflammation, 76 mono nuclear and neutrophilic inflammation of microvessels, 110 lymphocytic endotheliitis, 110 thrombotic microangiopathy, 116 cytoplasmic vacuolisation, 117 and (pulmonary) capillaritis.…”
Section: Coagulopathy and Endothelial Damagementioning
confidence: 99%
“…It has been observed that individuals with kidney disease are vulnerable to severe COVID-19. In another medical study (Sadegh Beigee et al 2020 ), damage to lung tissue biopsy samples of people who died due to COVID-19 was detected. Thus, it is hoped that when research is expanded, it will shed light on the development of effective treatment methods.…”
Section: Introductionmentioning
confidence: 96%
“…Among these symptoms, shortness of breath and dry cough caused by respiratory failure are the major causes of death. Unfortunately, Coronavirus sometimes appears to affect other essential organs, namely the heart, kidneys, brain, and lungs (Sadegh Beigee et al 2020 ). Despite all the information available about this virus, there are still many uncertainties about its behavior, virus-patient interaction, and pandemic process (Features n.d ).…”
Section: Introductionmentioning
confidence: 99%